Power 2 Gas: The green future Colombia needs: Proof of concept (2024)
Power to X is a concept that incurs in the transformation of the surplus electrical energy and transforming it into a gas so it could be stored as chemical potential energy and therefore be used as such or converted back to electricity. This process allows countries to bypass the extraction of methane from gas fields and acquire some level of independence from gas producing countries and companies. The process commences by separating water molecules through electrolysis into H2 and some other remanent, commonly O2. Then the hydrogen is stored as H2 or sent to facilities to undergo a process of methanation where it finally transmutes into methane. It can be mixed with other chemical agents to create a diverse portfolio of chemical compounds, such as ammonia, methanol, or e-fuel.